A comparative study on initial developments between explosive and nonexplosive cyclones off the East Asian coast in winter - Gao, Xiaoyu; Lu, Ping; Zhang, Shuqin; Hu, Yang; Fu, Gang; Sun, Xiaoyan; Zhang, Qiuyang (Frontiers in Earth Science, 2022)
Explosive cyclones (ECs) pose serious challenges for weather forecasting and significant threats to human life and property. In searching for the key points that make a cyclone go through explosive deepening off the East Asian coast, we present a statistical analysis of all the winter cyclones using 10 years of ERA5 reanalysis data with 1-h time resolution. The synoptic backgrounds are shown, and mechanisms of the initial developments of ECs and the non-explosive cyclones (or ordinary cyclones, OCs) are compared quantitatively in the perspective of potential vorticity (PV). The results show that among the identified 135 cyclones, 72 went through explosive growth, and 37.5/36.1/20.8/5.6% of these ECs are ranked as weak/medium/strong/super ECs. ECs feature stronger low-level baroclinicity and higher PV than OCs. The decomposition of local PV tendency shows the dominant role of the PV advection (with a correlation coefficient of 0.8). During the initial development, ECs have an average meridional temperature contrast 4 K larger than OCs within 20 latitudes at low troposphere in the upstream, due to a stronger cold advection. The upstream cold air increases upstream static stability, leading to the intrusion of higher PV along the steeper isentropic surfaces. Importance of the horizontal gradient of potential temperature is further proved by numerical experiments with the Weather Research and Forecast (WRF) model on typical winter ECs. In sensitivity experiments, the low-troposphere meridional temperature contrast decreasing by the average difference between ECs and OCs significantly decreases PV and stops the cyclones from explosive deepening. Despite the importance of diabatic processes in the deepening of mid-latitude cyclones emphasized by many studies, this study shows that the PV intrusion dominated by cold air mass is the key cause of winter explosive cyclogenesis in this region.